Threats Affecting the Construction Industries in The Libyan Jamahiriya Case Study at Hot Rolling Mill Factory - Ahmed, Hebatalrahman; Abu Ruwaila, Abdul Hadi Ali (Journal of Risk and Crisis Management, 2020)
This research deals with the problem of breakdowns and interruptions and their impact on the industrial system in the iron and steel industry, which considered as one of the industries related to the construction sector and automotive industries. The research is an applied study on the hot rolling mill factory of the Libyan Iron and Steel Company in Misurata. The study introduces analysis for maintenance programs and their economics related to breakdown and breakdown rates in the hot rolling factory in Misurata, which is the main producer of steel reinforcement and steel bars in the Libyan Jamahiriya. Malfunctions and breakdowns are studied through annual statistics reports stop in the previous years of the life of the factory, The effects of mechanical stops on the annual production amount in the factory were estimated and calculated statically, the research also discusses many concepts and strategies for new maintenance operations such as maintenance before malfunctions such as predictive maintenance and periodic maintenance. The research end with a group of conclusions and recommendations for the methods to overcome the problems of stoppages and breakdowns in steel mills, it is establishing a strategy for counting, assessing faults and developing maintenance systems in proportion to the age of the plant.